Bacterial Consortium and Microbial Metabolites Increase Grain Quality and Soybean Yield - Moretti, Luiz Gustavo [UNESP]; Crusciol, Carlos Alexandre Costa [UNESP]; Bossolani, João William [UNESP]; Momesso, Letusa [UNESP]; Garcia, Ariani [UNESP]; Kuramae, Eiko Eurya; Hungria, Mariangela (Springer Nature, 2020)
The effects of Bradyrhizobium inoculation on soybean growth and productivity are well known, but plant responses to consortia of other beneficial microbes and microbial molecules have not yet been well explored. Therefore, the main aim of this study was to evaluate the effect of different combinations of beneficial bacteria with and without microbial secondary metabolites (MSM) on two soybean cultivars in three cropping seasons under tropical field conditions. The bacterial consortia consisted of Bradyrhizobium japonicum (strain SEMIA 5079) plus Bradyrhizobium diazoefficiens (strain SEMIA 5080) inoculated with different combinations of Bacillus subtilis (strain QST 713), Azospirillum brasilense (strains Ab-V5 and Ab-V6), and MSM (metabolites enriched in lipo-chitooligosaccharides (LCOs) extracted from B. diazoefficiens (strain USDA 110) and from Rhizobium tropici (strain CIAT 889)). Standard inoculation of Bradyrhizobium combined with Azospirillum brasilense and microbial secondary metabolites increased leaf total N (7.1%), total P (11.1%), and N-ureide (16.5%); nodule number (NN, 26%) and dry weight (NDW, 22%); root (RDW, 15.4%) and shoot dry weight (SDW, 6%); 100-seed weight (3.7%); grain yield (up to 516 kg ha−1); grain crude protein concentration (2.4%); and the agronomic efficiency index (AEI) (11%). Inoculation with bacterial consortia and metabolites increased grain yield and quality, representing a promising technology for sustainable soybean cropping in tropical regions. [Figure not available: see fulltext.]
Keywords: Azospirillum brasilense; Bacillus subtilis; Bradyrhizobium diazoefficiens; Bradyrhizobium japonicum; Microbial metabolites; Rhizobium tropici